Aesthetic Concerns in Forensic Expertise - Two Case Reports - Aslan, Fatmagül (The Bulletin of Legal Medicine, 2022)
With the general laws of artistic creation, the theoretical science of beauty in art and life is aesthetics. As there are branches dealing with aesthetics in science and art, all branches can also have aesthetic aspects. Plastic, aesthetic and reconstructive surgery, which is a special field in Medical Science, deals with this issue. Those working in the field of forensic medicine contribute to the field by expressing their opinions about the situations where this aesthetics are impaired or the aesthetic expectations are not met, and by determining how living things or objects looked before through reconstruction studies. In the study, by presenting two cases with aesthetic intervention applied without illumination and consent, the human factor in aesthetics will be highlighted, and the points that need to be considered in forensic expertise will be emphasized.
Keywords: Aesthetics, Judicial, Medical malpractise